Faktor-Faktor yang Mempengaruhi Price of Book Value pada Perusahaan Sektor Consumer Non Cyclical di Bursa Efek Indonesia Periode 2018-2022 - Rachmawati, Luthfiah; Bakhri, Syaeful; Nursyamsudin, Nursyamsudin (AL-Muqayyad, 2024)
Company value is a descriptive view of the state of a company. The value of the company reflects the good management of its wealth management, which can be considered in measuring financial performance. This study set out to ascertain and examine the impact of capital structure, profitability, debt policy, and firm size on the value of non-cyclical consumer companies listed on the Indonesian stock exchange. With the following requirements: the firm must be registered on the IDX, produce financial reports consistently, turn a profit, and utilize the Rupiah currency. This study employs the purposive sample approach. Panel data regression analysis using Fixed Effect Model (FEM) estimate is the data analysis method that was employed. Eviews version 10 was utilized for testing. According to the study's findings, capital structure and profitability have a major and beneficial impact on a company's value. However, the size of the firm and its debt strategy don't really affect its worth.